Developmental differences in masked form priming are not driven by vocabulary growth - Bhide, Adeetee; Schlaggar, Bradley L.; Barnes, Kelly Anne (Frontiers in Psychology, 2014)
As children develop into skilled readers, they are able to more quickly and accurately distinguish between words with similar visual forms (i.e., they develop precise lexical representations). The masked form priming lexical decision task is used to test the precision of lexical representations. In this paradigm, a prime (which differs by one letter from the target) is briefly flashed before the target is presented. Participants make a lexical decision to the target. Primes can facilitate reaction time by partially activating the lexical entry for the target. If a prime is unable to facilitate reaction time, it is assumed that participants have a precise orthographic representation of the target and thus the prime is not a close enough match to activate its lexical entry. Previous developmental work has shown that children and adults' lexical decision times are facilitated by form primes preceding words from small neighborhoods (i.e., very few words can be formed by changing one letter in the original word; low N words), but only children are facilitated by form primes preceding words from large neighborhoods (high N words). It has been hypothesized that written vocabulary growth drives the increase in the precision of the orthographic representations; children may not know all of the neighbors of the high N words, making the words effectively low N for them. We tested this hypothesis by (1) equating the effective orthographic neighborhood size of the targets for children and adults and (2) testing whether age or vocabulary size was a better predictor of the extent of form priming. We found priming differences even when controlling for effective neighborhood size. Furthermore, age was a better predictor of form priming effects than was vocabulary size. Our findings provide no support for the hypothesis that growth in written vocabulary size gives rise to more precise lexical representations. We propose that the development of spelling ability may be a more important factor.